Full Outline of UnResponsiveness Score Versus Glasgow Coma Scale in Children With Nontraumatic Impairment of Consciousness. (October 2014) - Kochar, Gurpreet Singh; Gulati, Sheffali; Lodha, Rakesh; Pandey, RM
The study was designed to compare the Full Outline of UnResponsiveness score with Glasgow Coma Scale as a predictor of mortality and poor functional outcome at hospital discharge in children with nontraumatic impairment of consciousness. Seventy children aged 5 to 18 years admitted with impaired consciousness were enrolled. The scores were applied by the Pediatric Neurology fellow within 2 hours of admission. The primary outcome studied was in-hospital mortality. Receiver operating characteristic curves were used to compare the 2 scores. The area under the curves for Glasgow Coma Scale and Full Outline of UnResponsiveness scores were 0.916 and 0.940, respectively. However, the difference between the areas under curve for the 2 scores was not statistically significant (0.023; 95% confidence interval: –0.0115 to 0.058). Our data indicate that both the scores are good predictors for in-hospital mortality and functional outcome. However, no significant difference was observed between the ability of the 2 scores to predict the outcomes.